Knowledge, Perception, Attitude and Social Culture as Determinant of Male Participation in Family Planning - Puspita, Surya Dewi; Hernawati, Sri; Ningtyias, Farida Wahyu (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
a